The revised SAT score and its potential benefits for the admission of minority students to higher education - Maria Veronica Santelices; Mark Wilson (Arizona State University, 2015)
This paper investigates the predictive validity of the Revised SAT (R-SAT) score, proposed by Freedle (2003) as an alternative to compensate minority students for the potential harm caused by the relationship between item difficulty and ethnic DIF observed in the SAT. The R-SAT score is the score minority students would have received if only the hardest questions from the test had been considered and was computed using a formula score and a regression approach. In this article we examine the potential effects of using the R-SAT of minority students in the admissions decision to selective institutions, and its capacity to predict short and long-term academic outcomes as well as its potential benefits regarding differential prediction of college grades for minority students. To test this out, we examined the performance of the R-SAT score compared to the standard SAT score in a sample of graduates from California public schools and in a subsample of students who enrolled in the University of California. We found that, in terms of the potential for college admissions for minority students, prediction power and the issue of overprediction, the R-SAT score did not perform significantly better than the SAT score.